ASPEK PERSUASI DALAM PIDATO AJAKAN VAKSIN DI ERA PENDEMI COVID-19 - Widodo, Dhanu Priyo; Mantiri, Grace Janice Martha; Mukhlis, Abdul (STKIP Singkawang, 2024)
This research is aimed to describe the persuasive aspects of speech in inviting people getting Covid-19 vaccinated. In this research, the persuasive aspect focuses on presenting the content of the message which is divided into three parts. They are informational, emotional and motivational appeals. Furthermore, the research method being used is a descriptive method with content analysis techniques. The data source used is the speech inviting people to get the Covid-19 vaccinated made by President Joko Widodo. Meanwhile, the data used in this research are sentence fragments which are identified as presenting the content of the message. The data collection technique begins with the process of transliterating the speech inviting the Covid-19 vaccine delivered by Joko Widodo from oral form to written form. The next process is to create a categorization based on research need which is the presentation of the message content. Next, the data is analyzed using the stages of data collection, data reduction, and data analysis or interpretation. Furthermore, the findings showed that informational appeals dominate with a total of 147 data findings. This shows that the speech calling for a Covid-19 vaccination conveys a message that contains facts that are factual, objective, and tries to touch the audience so that the speaker hopes that listeners can participate in administering vaccines to limit the spread of the Covid-19 virus